HUBUNGAN ANTARA BATAS CAIR DAN INDEKS PLASTISITAS TERHADAP NILAI KOHESI TANAH LEMPUNG YANG DICAMPUR PASIR PANTAI DAN ABU KAYU PADA UJI DIRECT SHEAR - Heri Surahman; Wiji Lestarini (Device, 2023)
Aribaya – Kayuares Road, Banjarnegara Regency has poor soil carrying capacity and is clayey. This resulted in damage such as potholes, peeling asphalt and landslides. Therefore it is necessary to do research on soil types and soil cohesion values, one of which is using the Direct Shear test with a mixture ratio of 0%, 10%, 15%, 20% beach sand and 2.5%, 5%, 7.5% ash. wood. The research objective was to determine the effect of beach sand and wood ash on the type and value of soil cohesion through testing of physical and mechanical properties. The results showed that the soil classification according to USCS was classified as MH group soil, while the soil classification according to AASHTO was classified as group A-7-5. The results of testing the liquid limit, plastic limit and plasticity index, decreased in variations of the 20% beach sand and 2.5% mixture. Liquid limit value = 26.44%, plastic limit = 17.36%, plasticity index = 57.93%. The results of the Direct Shear test showed a decrease in soil cohesion value of 58% in a mixture of 20% beach sand + 2.5% wood ash. The greater the addition of sand content, the cohesion value (c) of the soil, liquid limit and plasticity index of the soil will decrease.